2021
DOI: 10.2147/ppa.s291255
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Dental Care in Individuals with Special Healthcare Needs in Qatif, Saudi Arabia: A Caregiver’s Perspective

Abstract: Access to dental care is a key factor influencing oral health outcomes. Individuals with special healthcare needs are at risk of not having access to dental care services which they need to maintain their oral health. This study assessed the magnitude of this problem and identified barriers responsible for the difficulties in accessing dental care in Qatif, Saudi Arabia, as reported by caregivers of individuals with special healthcare needs. Methods: This cross-sectional study collected data using a self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…Dental treatments such as dental fillings, crowns, and extraction were provided with a lower rate. These results align with the findings of other studies, in which a lack of dental care is evident among CSHCN [21,22,24,28,29]. Regarding treatment providers, agreeing with previous reports, pediatric dentists are the primary providers of dental care for CSHCN and very few general dentists provide such a treatment [19,20].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Dental treatments such as dental fillings, crowns, and extraction were provided with a lower rate. These results align with the findings of other studies, in which a lack of dental care is evident among CSHCN [21,22,24,28,29]. Regarding treatment providers, agreeing with previous reports, pediatric dentists are the primary providers of dental care for CSHCN and very few general dentists provide such a treatment [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…Fear of the dentist, child uncooperativeness and accessibility of dental clinics were the main barriers reported. Previous reports agree with this study, demonstrating that the inadequacy of dental care for CSHCN is a major unmet healthcare need [21,22,24,28,29]. Generally, dental care for CSHCN necessitates specialized knowledge, increased awareness and care, adaptation to specific medical conditions, and reconciling procedures outside of the usual routine [1].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This cross-sectional study is a part of a larger study that was conducted between February and April 2019 to investigate the oral health knowledge, barriers to access to care, and general health perception of special needs' caregivers population in Qatif city, Eastern Province of Saudi Arabia, with a population of about 524,400 [ 22 , 23 ]. Public schools with integrated special needs education, centers associated with the Ministry of Social Affairs, as well as charity organizations providing support for the care of individuals with special healthcare needs in Qatif were approached for the study.…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of research was carried out on children [11]. Studies have shown that people with special medical care needs may be less likely to access dental care [12] and a recent report has shown that people with Cystic Fibrosis may attend dental practices less frequently than is recommended [13].…”
Section: Introductionmentioning
confidence: 99%